Analisis Keuntungan Warung Puput Di Kelurahan Bahu Kecamatan Malalayang Kota Manado - Ahmad, Kundrat; Sondakh, Mex Frans Lodwyk; Rumagit, Grace Adonia Josefina (AGRI-SOSIOEKONOMI, 2024)
The purpose of this study was to analyze the profit of Warung Puput business in Bahu Village, Malalayang District, Manado City. The research was conducted for 2 months starting from January to February 2023. The research was conducted at Warung Puput business in Bahu Village, Malalayang District, Manado City. The research method used is a case study. The data used are primary data and secondary data, primary data obtained from direct interviews with the owner of Puput's warung business using a questionnaire as a tool in data collection. While secondary data comes from supporting data through books, journals, and scientific writings that can support research. This research uses descriptive analysis, the data obtained is then presented in tabulation to facilitate the delivery of research results. This research uses mathematical calculation analysis of total costs, revenue analysis, profit analysis. The results showed that the amount of profit of Warung Puput business in Bahu Village, Malalayang Subdistrict, Manado City can be categorized as a profitable business with a total income of IDR10.005.000 per week and a total cost of IDR6.872.489 per week, then an income of IDR3.132.511 per week is obtained.